Mechanistic evidence of widespread insecticide resistance among the Illinois West nile virus vectors Culex pipiens and Culex restuans - Kylee R. Noel; Chang-Hyun Kim; Chris M. Stone (Scientific Reports)
Abstract Mosquitoes are major vectors of diseases and a significant public health concern worldwide. Outbreak mitigation relies largely on insecticides, but the evolution of insecticide resistance threatens the effectiveness of such responses. Monitoring insecticide susceptibility is therefore vital for informed decisions regarding outbreak responses. This study examines resistance patterns to permethrin and malathion in West Nile virus vectors, Cx. pipiens and Cx. restuans, across Illinois from 2018 to 2020. CDC bottle bioassays were used to determine phenotypic resistance to each insecticide. Individuals from each sampling location were sequenced to determine the presence of kdr target-site mutations and assays were performed to determine increases in detoxification enzymes and insensitive acetylcholinesterase. Results showed variable resistance, with lowered mortality in most regions. The kdr mutation (L1014F) was detected in 50% of Cx. pipiens and was most prevalent in southern Illinois. Different mechanisms were predictive of resistance by species and insecticide. Permethrin resistance in Cx. pipiens was influenced by kdr-allele frequency and oxidase levels, while malathion resistance was linked to α- and β-esterase. For Cx. restuans α-esterase and oxidase levels were predictive of permethrin resistance while β-esterase and insensitive acetylcholinesterase levels influenced malathion resistance. These findings highlight population differences in kdr mutation rates and metabolic resistance, underscoring the importance of ongoing insecticide resistance monitoring for effective management strategies.